PERANCANGAN PATEEN COFFEE HOUSE DENGAN PENDEKATAN SENSE OF PLACE OLEH KONSULTAN ARSITEKTUR INTERIOR FK STUDIO - Frederick Kurniawan; Yusuf Ariyanto (KREASI, 2023)
The coronavirus pandemic is changing coffee business trends in 2021. Owners of coffee shops should anticipate increased competition for clients by providing high-quality coffee drinks, affordable prices, and simpler store concepts. Seeing this, interior architecture consultant FK Studio is here to help people get the ideal building design according to the design approach and sense of place owned by the company. This strategy was chosen since it is evident that modern society must keep up with the swift advancements of the times, and coffee is becoming increasingly common as a result of people’s demand for a gathering place where they can unwind, relieve stress, or even learn new things about the beverage. In contrast, an architectural design method called Sense of Place in Architecture concentrates on natural elements, human senses, and psychology, which bind people to that place. To achieve this, various design stages need to be carried out, starting from location observation and analysis, research, creativity, and development of design ideas, as well as the design finalization stage. The location of this project is on the edge of rice fields with a calm, comfortable, and natural atmosphere. Meanwhile, the desires and needs of visitors and owners of coffee houses Regarding design that is comfortable, calm, and appropriate to the context, the approach will be answered of place which is applied to architectural and interior design elements as well as the use of locations and surrounding areas to support the application of this approach.